Efeito da triiodotironina (T3) no desenvolvimento embrionário das larvas de pintado (Pseudoplatystoma coruscans), piracanjuba (Brycon orbignyanus) e dourado (Salminus maxillosus) - Landines Parra, Miguel Angel [UNESP] (2003)
This study investigated the effect of triiodothyronine (T3) applied to pintado Pseudoplatystoma coruscans eggs on the embryo development and initial growth of larvae. The work was conducted at Centro Nacional de Pesquisa de Peixes Tropicais (CEPTA), Pirassununga, and at Faculdade de Ciências Agrárias e Veterinárias da Universidade Estadual Paulista, Jaboticabal, SP. Fertilized eggs were divided in 6 portions and immersed for 15 min in different solutions of T3, forming the treatments: T1-no hormone; T2-0.01 ppm; T3-0.05 ppm; T4-0.1 ppm; T5-0.5 ppm and T6-1 ppm. After immersion, eggs were washed and incubated in plastic boxes. For the morphological analysis, eggs were collected after fertilization and at each 30 min until hour 6, and following at each 2 h until the hatching. Larvae were sampled at each 12 h until hour 72 and at 24 h until hour 168, for the weight and length determination and yolk sac volume calculation. The results were subjected to ANOVA and means compared to Tukey test (5%). The results showed that triiodothyronine did not affect the embryo development in any concentration tested. Regarding growth, it was higher in weight since hour 120 and in length after hour 144 in larvae produced by eggs exposed to hormone, especially in doses 0.1; 0.5 and 1 ppm. At the last sampling (hour168) there were no differences in length. At the hatching, the volume of yolk sac was lower in larvae from eggs exposed to the highest concentrations (0.1; 0.5 and 1 ppm), but the difference became more evident only at hour 48, when the structure was seen for the last time. Concluding, triiodothyronine, in the doses and application method utilized, did not affect the embryo development of pintado but stimulated the initial growth of larvae besides to accelerate the yolk sac resorption